Follow-up imaging in the first two years after nephrectomy for T1 RCC: Over-use or necessary care?. (March 2016) - Joshi, Shreyas S; Sohn, William S; Sun, Daniel; Clark, Peter E; Barocas, Daniel A; Resnick, Matthew J; Cookson, Michael S; Smith, Joseph A; Chang, Sam S
Objective: We sought to study patterns of imaging for follow-up after surgery for stage T1 renal cell carcinoma (RCC) at a single institution. We hypothesised that there would be significant variation in the use of surveillance imaging. Methods and materials: We evaluated the two-year follow-up of 317 consecutive patients undergoing radical or partial nephrectomy who were found to have pT1 RCC. Follow-up imaging data were collected. Surgical characteristics and tumour pathology data were analysed via a Poisson regression model to evaluate the incidence rate ratio for frequency of imaging based on each variable. Logistic regression was used to evaluate factors correlated with concordance with current imaging guidelines. Results: A total of 1016 imaging exams were performed after surgery on 268 patients. These studies identified four tumour recurrences: two local and two lung. The overall recurrence rate was 1.49%. Three recurrences were found within a two-year postoperative window, and one was recorded on the patient's last clinic note after two years. Of 66 imaging exams with findings suspicious for recurrence, 62 were found to be false positives. All statistical analyses on a subgroup of 162 patients with full two-year follow-up failed to demonstrate any correlation between clinicopathologic variables and the frequency of abdominal imaging or concordance with current imaging guidelines. Conclusions: Frequent follow-up imaging studies were obtained despite a low recurrence rate. There was a high rate of false-positive findings on routine exams. No clinicopathologic criteria were identified that were correlated with increased imaging frequency.